1995
DOI: 10.1055/s-2007-979946
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of the GLUT4 Glucose Transporter Protein in Adipose Tissue During Pregnancy

Abstract: Insulin resistance involves impaired activities of the glucose transport system in insulin target tissues. We therefore investigated the GLUT4 glucose transporter protein in adipose tissues from the pregnant women with normal glucose tolerance and from women with gestational diabetes mellitus, and compared these to nonpregnant women. Three groups of women were studied: nonpregnant women with normal glucose tolerance (N = 6), pregnant women with normal glucose tolerance (N = 6, gestational week 38.0 +/- 0.3), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 5 publications
0
21
0
5
Order By: Relevance
“…Expression of IRS-1 is reduced in experimental animals during pregnancy [19], a finding that has been confirmed in the skeletal muscle of normotolerant and GDM women in the last weeks of pregnancy: tyrosine phosphorylation of IRS-1 is reduced, compared to the prepregnancy state, by 28% in normal pregnancy and by 41% in a pregnancy with GDM [20]. Finally, in the late stage of pregnancy, and to a greater extent in GDM, a GLUT4 reduction has been reported [21][22][23]. The alterations of the insulinsignaling cascade is likely to be modulated by humoral factors.…”
Section: Insulin Resistancementioning
confidence: 61%
“…Expression of IRS-1 is reduced in experimental animals during pregnancy [19], a finding that has been confirmed in the skeletal muscle of normotolerant and GDM women in the last weeks of pregnancy: tyrosine phosphorylation of IRS-1 is reduced, compared to the prepregnancy state, by 28% in normal pregnancy and by 41% in a pregnancy with GDM [20]. Finally, in the late stage of pregnancy, and to a greater extent in GDM, a GLUT4 reduction has been reported [21][22][23]. The alterations of the insulinsignaling cascade is likely to be modulated by humoral factors.…”
Section: Insulin Resistancementioning
confidence: 61%
“…In both diseases, defects in glucose transporter expression have been observed (6,7). Taken together, these changes clearly demonstrate that estrogen plays an important role in glucose homeostasis.…”
Section: Muscle Glut4 Regulation By Estrogen Receptors Er␤ and Er␣mentioning
confidence: 76%
“…This process is mediated mainly by P 4 and, to a certain degree, E 2 . Because recent studies have shown that these steroid hormones play a role in glucose utilization by altering expression of several facilitative GLUTs in human breast cancer cell lines and murine muscle and adipose tissue (17,18,31,32), we used a primary culture of murine ESCs to examine the possible effects of P 4 and E 2 on glucose utilization in these cells.…”
Section: Discussionmentioning
confidence: 99%